Obesity as a barrier to living kidney donation: a center‐based analysis. (19th September 2013) - Sachdeva, Mala; Sunday, Suzanne; Israel, Ezra; Varghese, Jeny; Rosen, Lisa; Bhaskaran, Madhu; Molmenti, Ernesto P.; Mattana, Joseph
Abstract Background Obesity is a major epidemic and may present a significant barrier to living kidney donation. The purpose of our study was to determine the frequency of obesity as an exclusion factor and assess how often these donors lose weight and donate. Methods A single center, retrospective analysis of 104 potential living kidney donors between 2008 and 2012. Results Of the 104 donors, 19 (18%) had a normal body mass index (BMI) of <25. Eighty‐five of the 104 (82%) donors spanned the overweight to morbidly obese classifications. Thirty‐eight (37%) were overweight (BMI 25–29.9). Twenty‐four (23%) were categorized as class I obesity (BMI 30–34.9), 17 (16%) as class II obesity (BMI 35–39.9), and six (6%) as class III obesity (BMI >40). There were a total of 23 donors (22%) who were considered moderately and morbidly obese (BMI >35). Of these, only three (13%) succeeded at losing weight and donating. Conclusions Obesity may be a frequent barrier to living kidney donation, directly leading to exclusion as a potential kidney donor in about one in five instances. Successful weight loss leading to donation appears to be infrequent, suggesting need to address obesity in the donor population.